Formation of sensual culture of basic school students in the process of study of literature - Паламар, С. П. (Pedagogy of Higher and Secondary Education, 2013)
Palamar S. P. Formation of sensual culture of basic school students in the process of study of literature. The paper outlines the factors that influence the formation and enrichment of sensate culture elementary school students; analyzed in this process of studying literature. Proved the relationship of formation sensual culture elementary school students with the level of art education. The ability to analyze a literary work attributed to the structure of the reading competency of basic school pupils.